ความพึงพอใจของนักเรียนโรงเรียนอนุบาลขุนหาญ (สิ) ต่อการรับชมภาพยนตร์สั้นเรื่องอะไรดีและพอดีคำ - ศรีทา, อัจฉริยะ (Journal of Human and Society, Sisaket Rajabhat University, 2022)
การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อศึกษาความพึงพอใจของนักเรียนโรงเรียนอนุบาลขุนหาญ (สิ) ต่อการรับชมภาพยนตร์สั้นเรื่องอะไรดี และพอดีคำ ประชากรที่ใช้ในการศึกษาครั้งนี้ ได้แก่ นักเรียนที่เข้ารับการศึกษาในช่วงชั้นการเรียนรู้ที่ 2 ตามหลักสูตรการศึกษาขั้นพื้นฐาน อายุ 11 – 12 ปี ในสถานศึกษาระดับประถมศึกษา โรงเรียนอนุบาลขุนหาญ (สิ) อำเภอขุนหาญ จังหวัดศรีสะเกษ จำนวน 100 คน และ ได้ทําการศึกษาตั้งแต่วันที่ 10 มกราคม - 10 กุมภาพันธ์ 2561 เครื่องมือที่ใช้ใน การรวบรวมข้อมูล คือ แบบสอบถาม ผลการวิจัยสรุปได้ดังนี้ ด้านที่ 1 ความพอเพียง พบว่า 1) ภาพยนตร์มีเนื้อหาเรื่องความพอเพียง ระดับความพึงพอใจมากที่สุด 2) ภาพยนตร์สามารถถ่ายทอดเนื้อหาเรื่องความพอเพียง ได้อย่างน่าสนใจและเหมาะสม ระดับความพึงพอใจมากที่สุด 3) นักเรียนเข้าใจความหมายของ ความพอเพียง จากการชมภาพยนตร์ ระดับความพึงพอใจมากที่สุด 4) นักเรียนสามารถนำข้อคิดเรื่องความพอเพียง ประหยัดอดออม และการอยู่ร่วมกันกับผู้อื่น จากการรับชมภาพยนตร์ไปประยุกต์ใช้ในชีวิตประจำวันได้ ระดับความพึงพอใจมากที่สุด และ 5) นักเรียนสามารถนำข้อคิดเรื่องความพอเพียง จากการรับชมภาพยนตร์ไปถ่ายทอดให้กับเพื่อน ผู้ปกครอง และชุมชน อยู่ในระดับความพึงพอใจมาก ด้านที่ 2 การประหยัดอดออมได้แก่ 1) ภาพยนตร์มีเนื้อหาเรื่องการประหยัด อดออม ระดับความพึงพอใจมากที่สุด 2) ภาพยนตร์สามารถถ่ายทอดเนื้อหาเรื่อง การประหยัดอดออม ได้อย่างน่าสนใจและเหมาะสม ระดับความพึงพอใจมากที่สุด 3) นักเรียนเข้าใจความหมายของการประหยัดอดออม จากการชมภาพยนตร์ ระดับ ความพึงพอใจมากที่สุด 4) นักเรียนสามารถนำข้อคิดเรื่องประหยัดอดออม จาก การรับชมภาพยนตร์ไปประยุกต์ใช้ในชีวิตประจำวันได้ ระดับความพึงพอใจมากที่สุด 5) นักเรียนสามารถนำข้อคิดเรื่องการประหยัดอดออม จากการรับชมภาพยนตร์ ไปถ่ายทอดให้กับเพื่อน ผู้ปกครองและชุมชน ระดับความพึงพอใจมาก ด้านที่ 3 การอยู่ร่วมกับผู้อื่นพบว่า 1) ภาพยนตร์มีเนื้อหาเรื่องการอยู่ร่วมกัน กับผู้อื่นระดับความพึงพอใจมาก 2) ภาพยนตร์สามารถถ่ายทอดเนื้อหาเรื่องการอยู่ร่วมกันกับผู้อื่น ได้อย่างน่าสนใจและเหมาะสม ระดับความพึงพอใจมาก 3) นักเรียนเข้าใจความหมายของการอยู่ร่วมกันกับผู้อื่น จากการชมภาพยนตร์ ระดับความพึงพอใจมากที่สุด 4) นักเรียนสามารถนำข้อคิดเรื่องการอยู่ร่วมกันกับผู้อื่น จากการรับชมภาพยนตร์ไปประยุกต์ใช้ในชีวิตประจำวันได้ ระดับความพึงพอใจมากที่สุด 5)นักเรียนสามารถนำข้อคิดเรื่องการอยู่ร่วมกันกับผู้อื่น จากการรับชมภาพยนตร์ไปถ่ายทอดให้กับเพื่อน ผู้ปกครองและชุมชน ระดับความพึงพอใจมาก The purpose of this research was to study the satisfaction of the students from Khunhan (Si) Kindergarten School after watching the short films: What is good? (A-Rai D) and Fit (Por D Kam). The populations of this research were 100 students from age 11-12 years old which were in 2nd range of basic education in primary school: Khunhan (Si) Kindergarten School, Sisaket. The research was held during 10th January – 10th February 2018. The tool for gathering data was questionnaires. The author can summarize as follow ,The first dimension was sufficiency: 1) The sufficiency detail got highest satisfaction 2) The appropriate sufficiency explanation got highest satisfaction 3) The students’ understanding after watching short films got highest satisfaction 4) The applying of the students to use the ideas of sufficient living, living with others, and reasonable thinking after watching the short films got highest satisfaction and 5) The applying of the students after watching the short films to transfer to friends, parents and community got high satisfaction. The second dimension was economizing: 1) The economizing of the short films got highest satisfaction 2) The appropriate economizing explaining by the short films got highest satisfaction 3) The understanding economizing of the students after watching the short films got highest satisfaction 4) The applying of the students to use the idea of economizing got highest satisfaction and 5) The applying of the students about economizing after watching the short films to transfer to friends, parents and community got high satisfaction. The third dimension was living with others: 1) The detail of living with others got high satisfaction 2) The appropriate method of telling detail of living with others got high satisfaction 3) The understanding living with others of students after watching the short films got high satisfaction 4) The applying of the students to use the idea of living with others got highest satisfaction and 5) The applying of the students about living with others after watching short films to transfer to friends, parents and community got high satisfaction . The summary from questionnaires showed that after watching the short films: What is good? (A-Rai D) and Fit (Por D Kam), the populations expressed their satisfaction in high and highest levels. These 2 short films are the appropriate media to develop attitude and behavior about sufficiency, economizing, living with others which are easy to be understood. And, these can be applied to our daily life and transferred to others Students is the students in Prathom 6 at Anuban Khunhan Si School , Khun Han District, Sisaket Province. The short film media is to convey various stories in a way that is expressed as Animation for being a learning media for 2 researches were A-Rai D and Por D Kam. Learning is a process that causes humans to change their behavior. Humans can learn from hearing, touch, reading, seeing, as well as through the use of media as tools. Behavior is actions which are expressions of thoughts and needs of the mind that respond to stimuli. Which may be observed directly or indirectly Some features may be observed without tools or tools.